Applying Math with Python - Second Edition - Sam Morley (Packt Publishing, 2022)
"Applying Math with Python" is your guide to leveraging Python's powerful libraries for computational mathematics. With over 70 practical recipes, you'll gain hands-on experience solving real-world mathematical and statistical problems efficiently.What this Book will help me doUse Python libraries such as NumPy, SciPy, and Matplotlib to solve computational math problems.Apply techniques in calculus, statistics, and linear algebra to practical examples.Model and analyze networks using graph theory concepts.Develop forecasts and establish trends through statistical methods.Utilize Bayesian inference and MCMC for probability-based problem-solving.Author(s)None Morley specializes in computational mathematics and programming instruction. With years of experience teaching Python for data and mathematical applications, None brings clarity and practice-oriented learning into technical subjects. Morley focuses on effective pedagogy and practical relevance.Who is it for?This book is perfect for those looking to combine Python programming with mathematical problem-solving. Professional programmers and students will find the recipes clear and beneficial. A basic knowledge of mathematics is helpful, but familiarity with Python data structures is assumed. If exploring math in Python excites you, this book is tailored for you.